Essential role of prostaglandin E2 and the EP3 receptor in lymphatic vessel development during zebrafish embryogenesis - Ryo Iwasaki (Nature Portfolio, 2019)
Abstract Lymphatic endothelial cells arise from the venous endothelial cells in embryonic lymphatic development. However, the molecular mechanisms remain to be elucidated. We here report that prostaglandin (PG) E2 plays essential roles in the embryonic lymphatic development through the EP3 receptor, one of the PGE2 receptors. Knockdown of the EP3 receptor or inhibition of cyclooxygenases (COX; rate-limiting enzymes for PG synthesis) impaired lymphatic development by perturbing lymphatic specification during zebrafish development. These impairments by COX inhibition were recovered by treatment with sulprostone (EP1/3 agonist). Knockdown of the EP3 receptor further demonstrated its requirement in the expression of sex determining region Y-box 18 (sox18) and nuclear receptor subfamily 2, group F, member 2 (nr2f2), essential factors of the lymphatic specification. The EP3 receptor was expressed in the posterior cardinal vein (region of embryonic lymphatic development) and the adjacent intermediate cell mass (ICM) during the lymphatic specification. COX1 was expressed in the region more upstream of the posterior cardinal vein relative to the EP3 receptor, and the COX1-selective inhibitor impaired the lymphatic specification. On the other hand, two COX2 subtypes did not show distinct sites of expression around the region of expression of the EP3 receptor. Finally, we generated EP3-deficient zebrafish, which also showed defect in lymphatic specification and development. Thus, we demonstrated that COX1-derived PGE2-EP3 pathway is required for embryonic lymphatic development by upregulating the expression of key factors for the lymphatic specification.